Theoretical Study of Optimum Luminescent Down-Shifting Properties for High Efficiency and Stable Perovskite Solar Cells - Alexandre, Miguel Diogo Furtado (2019)
In recent years, the discovery of the excellent optical and electrical properties of perovskite materials made them one of focus of research in the area of photovoltaics, with its efficiency increasing significantly since its inception, in 2009. However, problems associated with the stability of these materials have hindered their widescale market application, with two examples being the UV degradation of the absorber material and the photoactivity, under 400 nm wavelengths, of TiO2 which is one of the main materials used as an electron transport layer in these cells. Consequently, different methods were studied to minimize this degradation. One example consists in using down-shifting materials that change the harmful UV radiation to higher wavelengths that have no effect on the cell stability. Thus, this work is focused in the theoretical study of the photocurrent gains that can be attained by emulating the changed spectrum resulting from applying these materials, as well as the reduction in the harmful effects of UV radiation on perovskite solar cells. This first case analyzed resulted in gains of around 1% for planar cells and around 2% for cells with photonic structures. For the second optimized case, one was able to obtain a general reduction in generation in TiO2 of one order of magnitude, coupled with a 80% reduction of perovskite’s UV absorption.